Sugar-sweetened beverages tax and obesity: Simulation of economic impacts from input-output analysis for Brazil - Cardoso, Larissa (2023)
Given the growing interest in taxing sugar-sweetened beverages, we estimated the effects of tax increase of sugary drinks for the Brazilian economy, focusing on the impact on household consumption, production, employment and tax revenues of the government. In order to identify these effects, we considered productive relations of SSB sector by calculating the forward and backward indices and employment multipliers based on the input-output matrix of Brazil. Additionally, we used the Leontief price model incorporating the disaggregation of household consumption vector by income decile in order to identify this effect in a distributional perspective. The results show a tax increase applied to the soft drinks industry generates a slight negative impact on the economy, but it reaches the expected effect: reduction of household consumption for this product. The distributional analysis shows the tax is clearly progressive over the decision, when measured by the compensatory variation.